Heterozygous cylindromatosis gene mutation c.1628_1629delCT in a family with brook-spiegler syndrome - Cintia Arjona Aguilera; Raquel De la Varga Martínez; Lidia Ossorio García; David Jimenez-Gallo; Cristina Albarrán Planelles; Mario Linares Barrios (Wolters Kluwer Medknow Publications, 2016)
Brooke-Spiegler Syndrome (BSS) is a rare genodermatosis characterized by the progressive formation of adnexal skin tumors in the scalp and face, mainly trichoepitheliomas, cylindromas, and spiradenomas. It has also been associated with salivary glands neoplasms. It is due to mutations in the tumor suppressor gene cylindromatosis (CYLD gene) localized on chromosome 16q12−q13. Around 93 mutations have been described. The study of CYLD gene in patients and their relatives is of vital importance to establish the molecular diagnosis and offer appropriate genetic counseling. There is a low risk of malignancy and patients require long-term follow-up. A case of BSS in a family is described. The existence of the genetic mutation at the CYLD gene c. 1628_1629delCT in three of the women affected was demonstrated. This mutation has only been described once in a previous study.